Surgical Correction of Scoliosis in Children with Spastic Quadriplegia: Benefits, Adverse Effects, and Patient Selection - Legg, Julian; Davies, Evan; Raich, Annie L.; Dettori, Joseph R.; Sherry, Ned (Evidence-Based Spine-Care Journal, 2014)
Study Rationale Cerebral palsy (CP) is a group of nonprogressive syndromes of posture and motor impairment associated with lesions of the immature brain. Spastic quadriplegia is the most severe form with a high incidence of scoliosis, back pain, respiratory compromise, pelvic obliquity, and poor sitting balance. Surgical stabilization of the spine is an effective technique for correcting deformity and restoring sitting posture. The decision to operate in this group of patients is challenging.Objectives The aim of this study is to determine the benefits of surgical correction of scoliosis in children with spastic quadriplegia, the adverse effects of this treatment, and what preoperative factors affect patient outcome after surgical correction.Materials and Methods A systematic review was undertaken to identify studies describing benefits and adverse effects of surgery in spastic quadriplegia. Factors affecting patient outcome following surgical correction of scoliosis were assessed. Studies involving adults and nonspastic quadriplegia were excluded.Results A total of 10 case series and 1 prospective and 3 retrospective cohort studies met inclusion criteria. There was significant variation in the overall risk of complications (range, 10.9−70.9%), mortality (range, 2.8−19%), respiratory/pulmonary complications (range, 26.9−57.1%), and infection (range, 2.5−56.8%). Factors associated with a worse outcome were a significant degree of thoracic kyphosis, days in the intensive care unit, and poor nutritional status.Conclusion Caregivers report a high degree of satisfaction with scoliosis surgery for children with spastic quadriplegia. There is limited evidence of preoperative factors that can predict patient outcome after scoliosis. There is a need for well-designed prospective studies of scoliosis surgery in spastic quadriplegia.
Keywords: cerebral palsy; scoliosis surgery; spastic quadriplegia; outcomes